Dry matter production of thirteen tropical legumes in association with Rhodes grass (Chloris gayana cCallide) on an acid soil in Ethiopia - Larbi, Asamoah; Lazier, John R.; Ochang, J.; Addie, A. (1995)
Swards of rhodes grass (Chloris gayana cCallide) planted alone or in association with 13 forage legumes (Aeschynomene falcata ILCA 12144; A. histrix ILCA 149; Desmodium ovalifolium ILCA 100; Macrotyloma axillare cArcher; Neonotonia wightii ILCA 9784, 10254 and 10688; Stylosanthes guianensis cCook and ILCA 11744; S. hamata cVerano and ILCA 167; and Zornia spILCA 10901 and 11362) on a low phosphorus, acid soil in southern Ethiopia were evaluated over 2 years for dry matter yield and legume content. Average dry matter yield of 2000 kg/ha in both years and legume contents of >20 percent and >30 percent in the first and second years, respectively, after establishment were used as measures of compatibility. Aeschynomene falcata ILCA 12144 and S. guianensis ILCA 11744 were potentially better than the others as compatible companion legumes in swards of rhodes grass and further evaluation seems warranted.